Childhood-onset growth hormone deficiency and the transition to adulthood: current perspective - Ahmid M; Ahmed SF; Shaikh MG (Dove Medical Press, 2018)
M Ahmid, SF Ahmed, MG Shaikh Development Endocrinology Research Group, School of Medicine, Dentistry and Nursing, University of Glasgow, Glasgow, UK Abstract: Childhood-onset growth hormone deficiency (CO-GHD) is an endocrine condition associated with a broad range of health issues from childhood through to adulthood, which requires particular attention during the transition period from adolescence to young adulthood. There is uncertainty in the clinical practice of the management of CO-GHD during transition regarding the clinical assessment and management of individual patients during and after transition to obtain optimal follow-up and improved health outcomes. Despite the availability of clinical guidelines providing the framework for transition of young adults with CO-GHD, there remains substantial variation in approaching transitional care among pediatric and adult services. A well-structured and coordinated transitional plan with clear communication and direct collaboration between pediatric and adult health care to ensure optimal management of adolescents with CO-GHD during transition is needed. Keywords: growth hormone deficiency, childhood-onset, transition, adolescents